Determination of an efficient irrigation schedule for the cultivation of rose cv. freedom under greenhouse conditions in colombia (2014)
An experiment on rose (Rosa sp.) cv. Freedom was performed in a greenhouse on the Bogota Plateau, Colombia, to identify an efficient irrigation regime for this crop. The tested treatments were based on three irrigation doses, applying different fractions of the estimated crop evapotranspiration (ETc), calculated using a class A evaporation tank: i) 100% ETc (ETc100), ii) 80% ETc (ETc80) and iii) 70% ETc (ETc70). During the entire experimental period, from mid-May to early September, the crop had a constant production of floral stems. In all of the irrigation treatments, the soil and plant water status were monitored using tensiometers and the midday stem water potential, respectively (Ψstem). In the fully irrigated roses, the actual water use was determined using a drainage lysimeter in order to obtain the local crop coefficients (Kc) by means of a water balance. From June to August, the obtained monthly Kc values varied between 1.10 and 1.26. Compared to the ETc100 treatment, 14.5 and 21.8% less water was applied in treatments ETc80 and ETc70, respectively. Despite this fact, no statistically significant differences were found among the treatments for rose production or quality. Finally, in the more irrigated roses, tight relationships between the stem water potential and vapor pressure deficit were obtained. The reported base-line equations can be used for predicting the optimum rose plant water status, depending on the environmental conditions. Overall, the reported results can be used for an efficient irritation schedule for rose crops under greenhouse conditions, using the local Kc and direct determinations of plant water status corrected for the evaporative demand.